Exacerbation of chronic myofascial pain during COVID-19 - Hala Karayanni; Amiel A. Dror; Daniel Oren; Eyal Sela; Igal Granot; Samer Srouji (Elsevier, 2021)
Objective: The COVID-19 pandemic-related restrictions on the public have led to changes in occupation status and societal behavior which may be linked with adverse effects on mental health. We hypothesized that elevated personal stress induced by COVID-19 may underlie pain exacerbation among individuals with chronic myofascial pain. Methods: Comprehensive myofascial pain questionnaire among 319 patients registered in our pain clinic. In total, 78 patients with TMD-associated pain responded and 113 patients with pain in other orofacial regions responded. Results: Patients with chronic TMD pain reported a higher self-rated stress level, which correlated with significantly increased pain intensity, and analgesic consumption. In contrast, patients experiencing non-TMD pain did not report of any increase pain, regardless of their stress levels. Conclusion: Significant correlation between self-perceived psychosocial stress levels and chronic myofascial pain exacerbation. Patients may benefit from early education and conservative intervention, and avoid uncontrolled increases in consumption of pain relief medication.